Aesthetics and Music - Hamilton, Andy (London Continuum, 2007)
"The Continuum Aesthetics" series looks at the aesthetic questions and issues raised by all major art forms. Stimulating, engaging and accessible, the series offers food for thought not only for students of aesthetics, but also for anyone with an interest in philosophy and the arts. "Aesthetics and Music" is a fresh and often provocative exploration of the key concepts and arguments in musical aesthetics. It draws on the rich heritage of the subject, while proposing distinctive new ways of thinking about music as an art form. The book looks at: the experience of listening; rhythm and musical movement; what modernism has meant for musical aesthetics; the relation of music to other 'sound arts'; improvisation and composition; as well as more traditional issues in musical aesthetics, such as absolute versus programme music and the question of musical formalism. Thinkers discussed range from Pythagoras and Plato to Kant, Nietzsche and Adorno. Areas of music covered include classical, popular and traditional music, and jazz. "Aesthetics and Music" makes an eloquent case for a humanistic, democratic and genuinely aesthetic conception of music and musical understanding. Anyone interested in what contemporary philosophy has to say about music as an art form will find this thought-provoking and highly enjoyable book required reading.
Keywords: Music philosophy and esthetics